The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ppc.12649
|View full text |Cite
|
Sign up to set email alerts
|

Self‐compassion and nursing competency among Japanese psychiatric nurses

Abstract: Purpose: This study examined the association of self-focus and self-compassion with nursing competency.Design and Methods: Data of 433 psychiatric nurses comprising demographics, other-consciousness, self-compassion, self-focus, and nursing competency were analyzed using the Other-Consciousness Scale (OCS), Self-Compassion Scale (SCS), Japanese version of the Rumination-Reflection Questionnaire (RRQ), and Oriented Problem Solving Behavior (OPSN).Findings: Higher internal aspect and lower fantastic aspect in OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…The number of years working in elderly care showed a signi cant correlation with clinical competence in the total sample, which is in line with earlier studies (50,51). However, we found signi cant correlations between clinical competence and working years for RNs but not for PNs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The number of years working in elderly care showed a signi cant correlation with clinical competence in the total sample, which is in line with earlier studies (50,51). However, we found signi cant correlations between clinical competence and working years for RNs but not for PNs.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the average age of nursing staff in LTC is relatively high (49)(50)(51). This was similar in our study, in which the mean age of all the participants was relatively high and a third of the PNs were aged between 51-60, which shows that the PNs' age was rather high.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data collection instruments were adapted from prior studies and consist of sections focusing on socio demographic characteristics and satisfaction with the psychiatric outpatient care [12,18]. To assess patient satisfaction, we have used a standardized satisfaction measurement tool developed for low income countries [19] and contained five-point Likert scale items, on scale "1" stood for rating of the item as "poor" while "2", "3", "4", and "5" stood for "fair", "good", "very good", and "excellent", respectively. The mean level of satisfaction was calculated by averaging their ratings for the parameters of measuring satisfaction.…”
Section: Data Collection and Managementmentioning
confidence: 99%
“…In general, self-compassionate individuals cope better with challenging situations [ 32 ] and are more open to accepting negative emotional and cognitive experiences [ 33 ]. The importance of self-compassion in relation to mental health has been reported in many different cultures including Japan [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%